Peran Pendidikan Moral-Etis dalam Mengembangkan Tugas Keterpanggilan Sebagai Pendeta - Claartje Pattinama (Jurnal Ilmiah Wahana Pendidikan, 2019)
This study aims to show the role of moral-ethical education for pastors in carrying out their calling duties as servants of the people, by referring to the pastor's competence to seek and save "lost sheep" but also efforts to protect people from various moral and ethical problems that often occur in congregation. The research method used is descriptive narrative method, which is a method that describes or describes experiences or events that will be examined in the form of narration or storytelling through a qualitative approach, so that it can be used to examine the status of a human group, an object, a set of conditions, a system of thought or an event class. This qualitative approach is used as a problem-solving procedure that will be examined by describing the subject-object situation, now based on the facts that appear in the study. The research was conducted to look at various moral and ethical violations that can occur to anyone, including the life of a pastor so it can be concluded that pastors have an obligation to develop their moral and ethical vocation by actively training themselves to assess morals and ethics in the community of believers , as well as guardians to maintain morals and ethics to later become a good example for the congregation and the community by responding positively to various violations that occur not only through the punishment approach, but also with an educational approach that is systemic, holistic, and comprehensive can be used as a way Exit.